Analisis Peran Kepala Perpustakaan Dalam Pengelolaan Perpustakaan Di SMA Negeri 1 Torjun - Siti Farida; Adis Safitri (AL -ALLAM, 2023)
This reaserch discusses the analysis of the role of the head of the library in library management at SMA Negeri 1 Torjun. The purpose of this study was to find out how the library management was carried out by the Head of the SMA Negeri 1 Torjun library from planning, organizing, implementing, and evaluating which was implemented in the SMA Negeri 1 Torjun library. Based on this, there are two research focuses that are the main studies in this study, namely: first, what are the steps taken by the head of library in library management?, second, what are the supporting and inhibiting factors in library management?. This study uses a descriptive qualitative approach in order to determine the role of the principal in library management at SMA Negeri 1 Torjun, this type of research is field research (Field Research).